The PBDE-209 Exposure during Pregnancy and Lactation Impairs Immune Function in Rats - Xianbao Liu; Hong Zhan; Xu Zeng; Chunfang Zhang; Dunjin Chen (Mediators of Inflammation)
In the present study, we assessed the treatment effects of PBDE-209 administration on the immune function in rats during pregnancy and lactation. We harvested the blood and organs for flow cytometry, viability assay, enzyme-linked immunosorbent assay, and histological evaluation. The results of this study were the PBDE-209 exposure during pregnancy and lactation impairs immune function in rats. The results may contribute to understanding the mechanism of PBDE-209 in immune function.